Bioactive Compound Profile and Biological Modeling Reveals the Potential Role of Purified Methanolic Extract of Sweet Flag (Acorus calamus L.) in Inhibiting the Dengue Virus (DENV) NS3 Protease-Helicase - Yuli Arif Tribudi; Ayu Tri Agustin; Dian Eka Setyaningtyas; Dwi Gusmalawati (Universitas Gadjah Mada, 2022)
Dengue fever is an infectious disease caused by the dengue virus, and there is no yet effective drug to treat this disease successfully. Our study aimed to identify the bioactive compounds of Acorus calamus L. and its potential role in inhibiting dengue virus NS3 protease-helicase. Liquid Chromatography-Mass Spectrometry analyzed phytochemical constituents. Drug-likeness of the predominant compound methanol extract of Acorus calamus L. was investigated through the SWISS ADME server. Complex molecular interactions were investigated by Hex 8.0 docking program and Discovery studio 2016. Our study revealed that the five largest phytochemicals in the extract were acoric acid, acorone, acoradin, acoronene, and calamendiol. All predominant compounds are potent to be developed as drug candidates. Molecular docking results showed that the five compounds bind to the Arg599, Pro291, Lys388, Pro431, and His487 of the dengue virus NS3 protease-helicase, the ligand-binding site that plays an essential role in viral replication. The ligand-protein binding pattern exhibited hydrogen and hydrophobic interactions. The interaction of the acoradin-NS3 protease-helicase complex had the lowest binding energy of -299.7 kcal/mol. In summary, we conclude that Acorus calamus L. extract may have prospects as a drug for dengue virus infection.